Karakterisasi, Identifikasi dan Uji Aktivitas Anti Jamur Minyak Atsiri Daun Jeruk Purut (Citrus hystrix) terhadap Aspergillus - Yanti, Rini; Wulandari, Pudji; Pranoto, Yudi; Cahyanto, Muhammad Nur (Fakultas Pertanian, Universitas Sam Ratulangi, 2017)
The objective of the work was to observe the physical properties, identify the components, and determine the antifungal activity of essential oil from lime leaves. Essential oil was extracted from lime leaves by water-steam distillation and determined its physical properties such as specific gravity, refractive index, and solubility in alcohol. The components of the oil were analyzed using GC-MS. Antimicrobial activity was evaluated against five species of Aspergillus, i.e.:A. niger, A.flavus, A.tamarii, A.Parasiticus, and A. candidus. Spores of the fungi were inoculated into plates of potato dextrose agar supplemented with lime leave essential oil at different concentration and incubate at 30oC for 7 days.Â Development of colonies was observed during the incubation. The essential oil from lime leaves had specific gravity of 0.8601, refractive index of 1.4523, and soluble in 2 volume and more 90% alcohol.The main compound in the essential oil was citronellal (87.9%). The oil also contained linalool (3.96%), transcaryophylene (2.17%), citronellil acetat (1.79%), and sabinene (1.78%). The oil showed antimicrobial activity against these five species of Aspergillus.Keywords: Lime leaves, essential oil, antifungal, Aspergillus